(untitled) (Revista Electrónica REDINE, 2021)
This review describes the process of creation and consolidation of MAYÉUTICA REVISTA CIENTÍFICA DE HUMANIDADES Y ARTES (ISSN 2477-9261) of the Universidad Centroccidental Lisandro Alvarado, Venezuela. This medium of scientific dissemination was founded in 2013, attached to the Dean of Humanities and Arts of said university, published biannually, it is indexed in Doaj, Revencyt, Redib, Clase and in Latindex Directory. Contributes to the dissemination of scientific works by national and international researchers on issues of social and / or human sciences, including the arts and literature, in spanish and english.